Pavões destinam tempo para a manutenção da sua plumagem ornamental? Tempo gasto pelo pavão Pavo cristatus (Lundiana: International Journal of Biodiversity, 2003)
Elaborate secondary sexual traits, such as the ornamental plumage of birds, appear to be favoured by female choice because they serve as honest advertisements of male quality. Elaborate plumage is thought to be an honest signal because it is energetically expensive to produce and to carry, and it may also increase the vulnerability of males to predators. According to several recent studies, the elaborate ornamental train of male blue peafowls (Pavo cristatus) appears to be such an honest signal. In this paper, I explore another potential cost of such plumage, which is the daily time and energy investment required to maintain the plumage in good condition. Since time devoted to maintenance cannot be devoted to feeding, vigilance, or other activities, the maintenance cost of ornamental plumage should reinforce the honesty of such plumage as an advertisement of male quality. I observed free-ranging peacocks for 30 hours at the Denver Zoo in June 2002 and April 2003. Preening, scratching and dusting took up more than 99% of maintenance time. Long bouts of maintenance behaviour were performed while peacocks were resting or standing, while short bouts occurred while peacocks were walking or feeding. No maintenance behaviours were observed while peacocks displayed their trains. Peacocks spent 14.9% of their total time budget on maintenance behaviours and 7.2% on displaying their trains, and 25.2% of their total grooming time on preening their trains. Consequently, peacocks not only incur the costs of producing and carrying their trains, but they also pay an additional maintenance cost. Hypotheses concerning the indicator mechanism of ornamental plumage need to consider these additional costs, as any additional cost should make the signal even more “honest”.